Problems of Online Learning During the Covid-19 Pandemic - Fathimah, Fathimah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The implementation of online learning is a learning model carried out during the pandemic. The application of online learning certainly requires the readiness of various parties, both from the school, office holders, and the students. There are things that must be considered in online learning, including the quality of teacher resources, both in terms of content and methodology as well as in terms of the use of information technology. In addition, students are also less active in participating in this online learning, either due to an unstable internet network or in terms of providing limited internet quota. The purpose of writing this article is to learn and understand the problems in learning activities during the pandemic, namely distance learning through online media so that students can follow it actively and interestingly. Distance learning (PJJ) through online media during the COVID-19 pandemic has led to various responses and changes to the learning system that can affect the learning process and the level of development of students in responding to material.